Final answer:
The discriminant of a quadratic equation informs us about the nature of its roots. By calculating the discriminant for each given equation, we categorize them accordingly: equations with discriminant greater than zero have two distinct real roots, equal to zero have one repeated real root, and less than zero have two complex roots.
Explanation:
The discriminant of a quadratic equation ax² + bx + c = 0 is given by the expression b² - 4ac. The value of the discriminant determines the nature of the roots of the equation. To find the type of roots for each given equation:
x² − 4x + 2: The discriminant is (-4)² - 4(1)(2) = 16 - 8 = 8, which is greater than zero, so this equation has two distinct real roots.
5x² − 2x + 3: The discriminant is (-2)² - 4(5)(3) = 4 - 60 = -56, which is less than zero, indicating two complex roots.
2x² + x − 6: The discriminant is (1)² - 4(2)(-6) = 1 + 48 = 49, also greater than zero, leading to two distinct real roots.
13x² − 4 = 0 has a discriminant equivalent to that for x² − 4/13 = 0, which is 0² - 4(1)(-4/13) = 16/13, which is greater than zero, so this equation will have two distinct real roots.
x² − 6x + 9: The discriminant is (-6)² - 4(1)(9) = 36 - 36 = 0, indicating one repeated root.
x² − 8x + 16: The discriminant is (-8)² - 4(1)(16) = 64 - 64 = 0, which means this equation has one repeated root.
4x² + 11 = 0 has a discriminant equivalent to that for x² + 11/4 = 0, which is 0² - 4(1)(11/4) = -11, less than zero, thus resulting in two complex roots.
Through the method of using the discriminant, we can determine the types of roots each quadratic equation will have.
he heights of △ABC are drawn from vertices A and C. These heights intersect at point M. Find m∠AMC, if m∠A=70° and m∠C=80°.
Answer: 150°
Step-by-step explanation:
In the given triangle ABC ∠A=70°, ∠C=80°
therefore ∠B=180-(∠A+∠C)=180-(70+80) [sum angle property of triangle]
⇒∠B=30°
Now, heights(altitude) are drawn from vertices A and C on respective bases
they intersect at a point M. Also, we know that heights are perpendicular on the bases.
Also, point of intersection of altitudes is called orthocenter.
Now since M is orthocenter, ∠ABC+∠AMC=180° (property of orthocenter in a triangle)
⇒30°+∠AMC=180°
⇒∠AMC=180°-30°=150°
Hence in the triangle ABC, ∠AMC=150°
"Angie read 3 books in 4 days, and each book contained 280 pages. if angie reads the same number of pages each day, how many pages did she read per day?"
Answer:210
Step-by-step explanation:
3 x 280 = 840
840 ÷ 4 = 210
Find the rule for (3,1) (6,2) (9,3) (12,4) (15,5)
Answer:
y = [tex]\frac{1}{3}[/tex] x
Step-by-step explanation:
Compare the values of y with the values of x for each ordered pair
x y
3 1 → y = 3 ÷ 3
6 2 → y = 6 ÷ 3
9 3 → y = 9 ÷ 3 = 3
12 4 → y = 12 ÷ 3 = 4
15 5 → y = 15 ÷ 3 = 5
The y value in each case is the x value divided by 3
Hence rule is
y = [tex]\frac{1}{3}[/tex] x
An estate of $656,000is left to three siblings. The eldest receives 6 times as much as the youngest. The middle sibling receives $15,000 more than the youngest. How much did each receive?
Step-by-step explanation:
If x is the amount the eldest receives, y is the amount the middle receives, and z is the amount the youngest receives, then:
x + y + z = 656000
x = 6z
y = z + 15000
Substituting the last two equations into the first:
(6z) + (z + 15000) + z = 656000
8z + 15000 = 656000
8z = 641000
z = 80125
Solving for the remaining variables:
x = 6z = 480750
y = z + 15000 = 95125
The eldest receives $480,750, the middle receives $95,125 and the youngest receives $80,125.
The youngest sibling receives $80,125, the middle sibling gets $95,125, and the eldest receives $480,750 from the $656,000 estate. The distribution complies with the stipulation that the eldest receives 6 times what the youngest does, and the middle sibling receives $15,000 more than the youngest.
The distribution of an estate of $656,000 among three siblings with specific conditions. Let's designate the amount the youngest sibling receives as y. According to the provided information, the eldest sibling receives 6 times as much as the youngest, meaning they receive 6y. The middle sibling receives y + $15,000. To find out how much each sibling receives, we need to solve the equation: y + 6y + (y + $15,000) = $656,000.
Add up the terms containing y: 8y + $15,000 = $656,000. Subtract $15,000 from both sides: 8y = $641,000. Divide both sides by 8 to find y:
y = $80,125.
Now, calculate each sibling's share:
The youngest receives y, which is $80,125.
The middle sibling receives y + $15,000, which is $95,125.
The eldest receives 6y, which is $480,750.
These calculations ensure that the total is $656,000, distributed according to the stipulated conditions.
what is the simplest form of the ratio 40:16?
which of the following is an arithmetic sequence
Answer:
C
Step-by-step explanation:
For it be an arithmetic sequence it must either be going up by the same number each time or down by the same number each time.
Lets look at the choices:
A. From 2 to 3 that went up by 1. But from 3 to 7, that doesn't continue to go up by 1. So this sequence is not arithmetic.
B. From 2 to 4, that went up by 2. But from 4 to 16, that doesn't continue to go up by 2. So this sequence is not arithmetic.
C. From 3 to 0, that goes down by 3. From 0 to -3, that goes down by 3. From -3 to -6, thar goes down by 3. This sequence is arithmetic.
Distance between points (-1,2) and (3,-5)
[tex]\huge{\boxed{\sqrt{65}}}\ \ \boxed{\text{approx. 8.06225775}}[/tex]
The distance formula is [tex]\sqrt{(x_2-x_1)^2 + (y_2-y_1)^2}[/tex], where [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex] are the points.
Substitute in the values. [tex]\sqrt{(3-(-1))^2 + (-5-2)^2}[/tex]
Simplify the negative subtraction. [tex]\sqrt{(3+1)^2 + (-5-2)^2}[/tex]
Add and subtract. [tex]\sqrt{4^2 + (-7)^2}[/tex]
Solve the exponents. [tex]\sqrt{16 + 49}[/tex]
Add. [tex]\sqrt{65}[/tex]
[tex]65[/tex] has no square factors, so this is as simple as the answer can get. You can use a calculator to find that [tex]\sqrt{65}[/tex] is approximately [tex]8.06225775[/tex].
The formula for distance between two points is:
[tex]\sqrt{(x_{2} -x_{1})^{2} + (y_{2} -y_{1})^{2}}[/tex]
In this case:
[tex]x_{2} =3\\x_{1} =-1\\y_{2} =-5\\y_{1} =2[/tex]
^^^Plug these numbers into the formula for distance like so...
[tex]\sqrt{(3 -(-1))^{2} + (-5-2)^{2}}[/tex]
To solve this you must use the rules of PEMDAS (Parentheses, Exponent, Multiplication, Division, Addition, Subtraction)
First we have parentheses. Remember that when solving you must go from left to right
[tex]\sqrt{(3 -(-1))^{2} + (-5-2)^{2}}[/tex]
3 - (-1) = 4
[tex]\sqrt{(4)^{2} + (-5-2)^{2}}[/tex]
-5 - 2 = -7
[tex]\sqrt{(4)^{2} + (-7)^{2}}[/tex]
Next solve the exponent. Again, you must do this from left to right
[tex]\sqrt{(4)^{2} + (-7)^{2}}[/tex]
4² = 16
[tex]\sqrt{16 + (-7)^{2}}[/tex]
(-7)² = 49
[tex]\sqrt{(16 + 49)}[/tex]
Now for the addition
[tex]\sqrt{(16 + 49)}[/tex]
16 + 49 = 65
√65 <<<This can not be further simplified so this is your exact answer
Your approximate answer would be about 8.06
***Remember that the above answers are in terms of units
Hope this helped!
~Just a girl in love with Shawn Mendes
What is the common difference of the sequence?
-4,-2, 0, 2, 4,.
d = - 2
d= 2
d = 2
d = 4
d = -4
Answer:
d= 2
Step-by-step explanation:
To find the common difference, take the second term and subtract the first
-2 - (-4)
-2+4 = 2
We add 2 each time
Lets check
Take the third term and subtract the second
0- -2
0+2 =2
The common difference is 2
EMERGENCY!!! SOMEONE HELP ASAP
Answer:
B
Step-by-step explanation:
Matrices are equal when they are of the same order and their corresponding entries are equal.
This is the case for the given matrix and matrix B
Answer:
The second option.
Step-by-step explanation:
It is the one that is marked.
The elements are the same and in the same location.
What is the difference between the absolute value of 4 and the absolute value of –3?
A) 1
B) 4
C) 7
D) 8
IM TIMED!!!!
Answer:
A) 1
Step-by-step explanation:
|4| - |-3|
4 - 3
1
what is the simplified form of 4x+2/x+5 plus 3x-1/x+5
[tex]\bf \underset{\textit{same denominator}}{\cfrac{4x+2}{x+5}+\cfrac{3x-1}{x+5}}\implies \cfrac{(4x+2)+(3x-1)}{x+5}\implies \cfrac{7x+1}{x+5}[/tex]
Answer:
(7x+1)/(x+5)
Step-by-step explanation:
4x+2 3x-1
-------- + ----------
x+5 x+5
Since the denominator is the same, we can add the numerators
4x+2 + 3x-1
-----------------------
x+5
Combine like terms
7x+1
-----------------------
x+5
what is a quadradic function
Answer: It is a polynomial function of degree 2 and whose graph is a parabola.
Step-by-step explanation:
By definition a quadratic function is a polynomial function of degree 2 and whose graph is a parabola.
The Standard form of a quadratic function is:
[tex]y= ax^2 + bx + c[/tex]
Where "a", "b" and "c" are real numbers ([tex]a\neq0[/tex])
The Vertex form of a quadratic function is:
[tex]y=a(x-h)^2+k[/tex]
Where the point (h,k) is the vertex of the parabola.
The Intercept form of a quadratic function is:
[tex]y=a(x-p)(x-q)[/tex]
Where "p" and "q" are the x-intercepts.
Final answer:
A quadratic function is a second-order polynomial of the form f(x) = ax² + bx + c, whose graph is a parabola. The solutions of quadratic equations are found by various methods to determine the roots or zeros of the function.
Explanation:
A quadratic function is a type of mathematical function that can be represented in the form f(x) = ax² + bx + c, where a, b, and c are constants, and a ≠ 0. This form is a second-order polynomial, as its highest exponent is 2. The graph of a quadratic function is a parabola, which can open upwards or downwards, depending on the sign of the a coefficient.
The solution of quadratic equations refers to finding the values of x that make the equation equal to zero. These solutions are also known as roots or zeros of the function.
To solve a quadratic equation, one can use different methods such as factoring, completing the square, using the quadratic formula, or graphing. Each of these methods provides a way to find the roots of the quadratic function.
PLEASE HELP EMERGENCY!!!!
Answer:
D
Step-by-step explanation:
Matrices are equal when they are of the same order and their corresponding entries are equal.
This is the case with the given matrix and matrix D
AD and MN are chords that intersect at point B what is the length of line segment MN?
Answer:
[tex]MN=18\ units[/tex]
Step-by-step explanation:
we know that
The Intersecting Chord Theorem, states that When two chords intersect each other inside a circle, the products of their segments are equal.
so
In this problem
[tex]AB*BD=MB*BN[/tex]
substitute
[tex](9)(x+1)=(x-1)(15)\\ \\9x+9=15x-15\\ \\15x-9x=9+15\\ \\ 6x=24\\ \\x=4\ units[/tex]
Find the length of line segment MN
[tex]MN=MB+BN=(x-1)+15=x+14[/tex]
substitute the value of x
[tex]MN=4+14=18\ units[/tex]
Answer:
MN = 18
Step-by-step explanation:
AD and MN are two chords intersecting inside the circle at point B.
As we know from intersecting chords theorem.
AB × BD = BN × BM
So 9(x-1) = 15 (x-1)
9x + 9 = 15x - 15
15x - 9x = 15 + 9
6x = 24
x = 4
and MN = (x-1) + 15
= (x + 14)
= 4 + 14 ( By putting x = 4 )
= (18)
Therefore, MN = 18 is the answer.
12x^ay^b / ( - 6x^ay )
Answer:
[tex]-2y^{b-1}[/tex]
Step-by-step explanation:
[tex]\frac{12x^ay^b}{-6x^ay}[/tex]
In multiplication of fractions you can do this:
[tex]\frac{a}{c} \cdot \frac{b}{d}=\frac{a \cdot b}{c \dot d} \text{ or the other way around } \frac{a \cdot b}{c \dot d}=\frac{a}{c} \cdot \frac{b}{d}[/tex].
So that is exactly what we are going to do here:
[tex]\frac{12x^ay^b}{-6x^ay}[/tex]
[tex]\frac{12}{-6} \cdot \frac{x^a}{x^a} \cdot \frac{y^b}{y}[/tex]
We know that 12 divided by -6=12/-6 =-2.
We also know assuming x isn't 0 that x^a/x^a=1.
On the last fraction, the only thing you can do there to simplify is use the following law of exponents: [tex]\frac{v^m}{v^n}=v^{m-n}[/tex].
So we have
[tex]\frac{12x^ay^b}{-6x^ay}[/tex]
[tex]\frac{12}{-6} \cdot \frac{x^a}{x^a} \cdot \frac{y^b}{y}[/tex]
[tex](-2) \cdot (1) \cdot (y^{b-1})[/tex]
Simplifying a bit and leaving out the ( ).
[tex]-2y^{b-1}[/tex]
PLEASE HELP ASAP!
For what value of x will the output to the exponential equation, y=3.80e^-0.20x, be equal to 2?
a.3
c.2
b.4
d.1
Answer:
2
Step-by-step explanation:
1) Take the natural log of both sides, obtaining:
-0.20x + ln 3.80 = ln 2
2) Group the ln terms on the right side: -0.20x = ln 2 - ln 3.80
3) Find the natural logs of 2 and 3.80 and combine them: -0.408, so that we have 0.20x = 0.408.
4) Solving for x, we get 2.03, or approx 2 (Answer C)
Answer:
a. 3 is the closest choice.
Step-by-step explanation:
2 = 3.80 e^-0.20x
e^-0.20x = 2/3.8
Taking logs:
-0.20x = ln(2/3.8) = -0.64185
x = 3.2.
Simplify each expression. e^(ln 1) = e^(ln 5x) =
[tex]\bf \textit{Logarithm Cancellation Rules} \\\\ log_a a^x = x\qquad \qquad \stackrel{\textit{we'll use this one}}{a^{log_a x}=x} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ e^{\ln(1)}=e^{\ln(5x)}\implies e^{\log_e(1)}=e^{\log_e(5x)}\implies 1=5x\implies \cfrac{1}{5}=x[/tex]
Answer: it’s 1 and 5x on edg
Step-by-step explanation:
what is the recursive formula for this geometric sequence -2, -16, ...
[tex]\displaystylea_1=-2\\r=8\\a_n=8a_{n-1}\\\\\left \{ {{a_1=-2} \atop {a_n=8a_{n-1}}} \right.[/tex]
Answer: The sequence is: An = -2*8^(n-1)
Step-by-step explanation:
 geometric sequence is of the form:
An = a*r^(n-1)
where can be any positive integer number.
here the first two numbers are -2 and -16, so we have that:
A1 = a*r^(0) = a = -2
now, we know that our sequence is of the form:
An = -2*r^(n-1)
now, for n= 2 we have that:
A2 = -2*r^(1) = -2*r = -16
r = -16/-2 = 8
now we have determinated our sequence:
An = -2*8^(n-1)
pLz help
Graph the linear equation. Find three points that solve the equation, then plot then on the graph.
x -3y= -6
Answer:
So you will want to graph the following 3 points:
(0,2)
(3,3)
(-3,1)
Then connect the points.
Step-by-step explanation:
So we have the equation x-3y=-6.
I'm going to solve for y once so I don't have to do it 3 times when choosing a value for x.
x-3y=-6
Subtract x on both sides:
-3y=-x-6
Divide both sides by -3:
[tex]y=\frac{-x}{-3}+\frac{-6}{-3}[/tex]
Simplify where you can:
[tex]y=\frac{1}{3}x+2[/tex]
So since this in the slope-intercept form, y=mx+b where slope is m and b is y-intercept we have that (0,2) is on our line. If you plug in 0, you will get 2 like this y=1/3 (0)+2=0+2=2.
Now I'm going to choose easy values to plug in, ones that are divisible by 3 since x is being multiplied by 1/3.
So if x=3, then [tex]y=\frac{1}{3}(3)+2=1+2=3[/tex], so (3,3) is on the line.
So if x=-3, then [tex]y=\frac{1}{3}(-3)+2=-1+2=1[/tex]. so (-3,1) is on the line.
So you will want to graph the following 3 points:
(0,2)
(3,3)
(-3,1)
1200 mm long and 800 mm wide. What is the area in square meters
Answer: [tex]0.96\ m^2[/tex]
Step-by-step explanation:
We can make the conversion from milimeters to meters (Remember that [tex]1m=1,000\ mm[/tex]). Then:
[tex]1,200\ mm[/tex] to [tex]m[/tex]:
[tex](1,200\ mm)(\frac{1\ m}{1,000\ mm})=1.2\ m[/tex]
[tex]800\ mm[/tex] to [tex]m[/tex]:
[tex](800\ mm)(\frac{1\ m}{1,000\ mm})=0.8\ m[/tex]
Now, we need to use this formula for calculate the area of a rectangle:
[tex]A=lw[/tex]
Where "l" is the lenght and "w" is the width.
Knowing that:
[tex]l=1.2\ m\\w=0.8\ m[/tex]
We can substitute values into the formula. Then we get:
[tex]A=(1.2\ m)(0.8\ m)\\\\A=0.96\ m^2[/tex]
Final answer:
The area of the rectangular shape is 0.96 square meters.
Explanation:
To find the area of a rectangle, we multiply its length by its width. Given that the length is 1200 mm and the width is 800 mm, we can convert these measurements to meters by dividing each measurement by 1000. So, the length in meters is 1.2 m and the width in meters is 0.8 m. To find the area in square meters, we multiply the length and width in meters: Area = 1.2 m × 0.8 m = 0.96 m².
Find the distance between the points (6, -4) and (0, 5).
Answer:
3 square root 13
Step-by-step explanation:
I used the distance formula and I got this answer.
Distance is the length of the path linking two sites is the distance between them.
How to solve ?Distance between two points is solved by formula
[tex]=\sqrt{(x1-x2)^2 +(y1-y2)^2}\\=\sqrt{(6-0)^2+(-4-5)^2} \\=\sqrt{36+81} \\=\sqrt{117} \\=10.81[/tex]
Hence distance between points is 10.81
Learn more about distance
https://brainly.com/question/17273444
#SPJ2
Learn more about distance
https://brainly.com/question/2854969
#SPJ2
product of (6+i)(2+9i)
Answer:
(6 + i)(2 + 9i) = 3 + 56iStep-by-step explanation:
Use FOIL: (a + b)(c + d) = ac + ad + bc + bd
and i² = -1
(6 + i)(2 + 9i) = (6)(2) + (6)(9i) + (i)(2) + (i)(9i)
= 12 + 54i + 2i + 9i²
= 12 + 54i + 2i + 9(-1)
= 12 + 54i + 2i - 9 combine like terms
= (12 - 9) + (54i + 2i)
= 3 + 56i
[tex](6+i)(2+9i)=18+54i+2i-9=9+56i[/tex]
does anyone know this????????
Answer:
3
______
4 | 12
-12
-----
0
Step-by-step explanation:
12/4
The top number always goes inside (larger or not), and the bottom number always goes on the outside (larger or not).
______
4 | 12
Ask yourself how many 4's are in 12.
Let's see one 4 is just 4.
We can probably do more 4's than that.
Two 4's gives us 4+4=8.
Let's see if we can put one 4 in there.
Three 4's gives us 4+4+4=12.
So we can fit three 4's into 12 and there is nothing left over.
3
______
4 | 12
-12 (since 4 times 3 or 4+4+4 is 12)
-----
0
Need help. Thanks for helping me.
Answer:
F 4 ^ -2
Step-by-step explanation:
4 ^ -5
-----------------
4^-3
We know that a^b/ a^c = a^ (b-c)
4 ^ (-5 - -3)
4 ^ (-5 +3)
4 ^ (-2)
1. Donna bought a coat on sale for $60.
That was 25% off ( less than the regular price).
What was the regular price?
Answer:
$240
Step-by-step explanation:
If x is the missing number and 25% equals to 1/4 then 1/4 times x equals 60.
Then once you multiply x on both sides you get $240.
Simplify
3 to the negative power of 9
over 3 to the negative power of 12
Answer:
27
Step-by-step explanation:
3^-9/ 3^-12
Simply change the division into multiplication. The denominator will become numerator. We are doing so because the base are same.
3^-9 * 3^12
Negative sign of power 12 become positive
Add the powers because the base is same.
3^-9+12
3^3
3^3 means multiply 3 three times
3*3*3
=27....
Answer:
3^3 In scientific notation terms
Step-by-step explanation:
First let's look at this in a little more simple way
[tex]\frac{3^{-9}}{3^{-12}}[/tex]
there so know we can start,
First since the main number is 3, put that away to the side for now:
3<---------- [tex]\frac{-9}{-12}[/tex]
Then, we need to replace the / symbol or the fraction with a subtraction equation:
[tex]^{-9-(-12)}[/tex]
Next, we need to simplify:
[tex]^{-9 + 12}[/tex]
Then, simplify some more and you should get:
[tex]^{3}[/tex]
Finally, get back the original 3 and combine it with the smaller 3:
[tex]3^{3}[/tex]
THANK YOU! Please Thanks, Vote 5, Thanks on my profile, and Friend!
Pls Brainliest! It would mean a lot! ; )
In triangle ABC, a = 3, b = 5, and c = 7. Find the approximate value of angle A. 22° 38° 142° 158°
Answer:
B.
Step-by-step explanation:
B.
Answer:
22
Step-by-step explanation:
law cosines
a^2=b^2+c^2 - 2bc cos A
plug in numbers
21.7 ish
round
22
Need answer to A and B!
Answer:
a) [tex]\frac{14}{285}[/tex]
b) [tex]\frac{11}{57}[/tex]
Step-by-step explanation:
We are given that a committee of three people is selected at random from a set of eight teachers, seven parents of students, and five alumni.
We are to find:
a) the probability the committee consists of all teachers is:
Number of ways to select three that are all teachers = [tex]8C3[/tex]
Number of ways to select three randomly = [tex]20C3[/tex]
P (3 all teachers) = [tex]\frac{8C3}{20C3}[/tex] = [tex]\frac{14}{285}[/tex]
b) the probability the committee has no teachers is:
Number of ways to select three that it has no teachers = [tex]12C3[/tex]
Number of ways to select three randomly = [tex]20C3[/tex]
P (no teachers) = [tex]\frac{12C3}{20C3}[/tex] = [tex]\frac{11}{57}[/tex]
While shopping at the grocery store, Dan decides to estimate the amount of money he will have to pay for the items he wants to buy. He rounds the individual price of each item to the nearest dollar and then adds up the numbers in his head. Dan adds the following items to his shopping cart: one carton of milk for $\$3.58$, one box of cookies for $\$2.97$, one loaf of bread for $\$2.17$, and one pineapple for $\$2.54$. According to Dan's estimate, how many dollars will he be spending at the store?
Answer:
12 dollars
Step-by-step explanation:
Mile 3.58 rounds to 4 dollars
cookies 2.97 rounds to 3 dollars
bread 2.17 rounds to 2 dollars
pineapple 2.54 rounds to 3 dollars
Adding the whole dollar amounts
4+3+2+3 = 12 dollars
Solution:
Dan will round the price of each item to the nearest dollar. So, the price of milk is rounded to $4, the price of cookies is rounded to $3, the price of bread is rounded to $2, and the pineapple's price is rounded to $3. Adding these numbers up, we get 4+3+2+3=12.Therefore, Dan estimates that he will spend about 12 dollars at the store.
simplify the following fraction 2/5+4/6-1/3
Answer:
11/15
Step-by-step explanation:
First, get a common denominator of 30. 2/5 becomes 12/30. 4/6 becomes 20/30. 1/3 becomes 10/30.
Now we can add and subtract accordingly.
12/30 + 20/30 = 32/30.
32/30 - 10/30 = 22/30.
Finally, simplify the fraction.
22/30 becomes 11/15 when each number is divided by 2.
Answer: [tex]\frac{11}{15}[/tex]
Step-by-step explanation:
The first step is to find the Least Common Denominator of the fractions. Descompose each denominator into its prime factors and muliply the commons and non-commons with the least exponent. Then:
[tex]5=5\\6=2*3\\3=3\\\\LCD=2*5*3=30[/tex]
Divide each denominator by the LCD and multiply this quotient by the corresponding numerator, add the products and then reduce the fraction.
Therefore you get:
[tex]=\frac{(2*6)+(4*5)-(1*10)}{30}=\frac{12+20-10}{30}=\frac{22}{30}=\frac{11}{15}[/tex]